Huge Gastric Trichobezoar Requiring Surgical Intervention in an Underweight Adolescent Female - Al Shibli, Nasib; Ijaz, Tariq; Alsharari, Nayel Hamed; Meer, Tooba; Mohammad, Alshammari Abdullaziz; Aldaham, Tamam Abdulrahman; Ahmed, Mahmoud Abdou Yassin (European Journal of Applied Sciences, 2025)
Trichotillomania was recognized as a psychological disorder characterized by the compulsive urge to pull out one’s own hair, leading to noticeable hair loss. When ingested, this hair accumulated in the stomach and formed a trichobezoar — a rare and fascinating condition. Most cases of trichobezoar occurred in young female patients with underlying psychiatric disorders. We reported a case of an 18-year-old underweight female who presented with a two-month history of upper abdominal pain, intermittent vomiting, and epigastric discomfort. After two unsuccessful treatment attempts due to the size of the mass, surgical intervention was performed to remove the trichobezoar. Postoperatively, she was advised to receive intravenous antibiotics for one week due to the risk of infective endocarditis, which was justified by her history of congenital cardiac disease. Surgical removal remained the mainstay of treatment for trichobezoar. It was important to note that most patients had associated psychiatric or social issues. Therefore, a multidisciplinary approach was considered essential to prevent recurrence.